ANALISIS PENGEMBANGAN OBJEK WISATA UNTUK MENINGKATKAN KUNJUNGAN WISATAWAN PADA TAMAN MARGASATWA DAN BUDAYA KINANTAN KOTA BUKITTINGGI PROVINSI SUMATERA BARAT - Anggraini, Dewi; Kumala, Vina (Ensiklopedia Sosial Review, 2021)
The city of Bukittinggi as one of the largest tourist cities in West Sumatra has a leading tourist attraction which is one of the oldest zoos in Indonesia. This zoo also displays various Minangkabau cultural attractions, therefore the government named this zoo Kinantan Wildlife and Culture Park (Taman Margasatwa dan Budaya Kinantan). Based on preliminary observations, data shows that the number of tourist visits to Kinantan is not proportional to the level of tourist visits to the City of Bukittinggi. Therefore, an in-depth research is carried out on the development of facilities and the role of the government in that development. This study uses descriptive qualitative methods, with data collection techniques through observation, interviews, and documentation. The results showed that the analysis showed that the role of government in developing Kinantan, namely as a motivator, facilitator, and dynamist has been running well and can increase the number of tourist visits.